IMF Staff papers : Volume 19 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1972)
This paper discusses the underlying objectives of the exchange rate regime are necessarily related to broader objectives of the international financial system and the international economy. The exchange rate regime should help to promote a satisfactory working of the adjustment process. The exchange rate regime should help to promote, or at least support, the pursuit of economic and financial policies that contribute to countries' domestic objectives, as regards both real economic variables and financial variables, notably including the degree of price stability. Attainment of the underlying objectives for the exchange rate regime suggests a number of instrumental or operational desiderata, which are listed below without regard to potential conflict between them and therefore without consideration of any trade-off among themselves. A system of adjustable parities and narrow margins should score well on the objective of exchange stability, provided that the adjustments are not too large or too frequent.